Kepuasan Kerja Dipengaruhi Oleh Disiplin Kerja, Komunikasi, Dan Stres Kerja Pada Pegawai Dinas Kesehatan Kota Balikpapan - Agni Prastistha, Erica; Ariani, Misna; Arrywibowo, Imam (Jurnal GeoEkonomi, 2025)
This study aims to analyze the influence of Work Discipline, Communication, and Work Stress on Job Satisfaction of Employees of the Balikpapan City Health Office. The type of research used is quantitative research. The sampling technique in this study is purposive sampling with a sample of 69 employees of the Balikpapan City Health Office. The data collection method was carried out by distributing questionnaires. This research uses Smart-PLS in managing data. The results of this study show that the variable of work discipline has a significant effect on the job satisfaction of employees of the Balikpapan City Health Office. Communication variables did not have a significant effect on the job satisfaction of employees of the Balikpapan City Health Office. The variable of work stress has a significant effect on the job satisfaction of employees of the Balikpapan City Health Office.